Bordetella pertussis infection or vaccination substantially protects mice against B. bronchiseptica infection. - Elizabeth M Goebel; Xuqing Zhang; Eric T Harvill (PLoS ONE)
Although B. bronchiseptica efficiently infects a wide range of mammalian hosts and efficiently spreads among them, it is rarely observed in humans. In contrast to the many other hosts of B. bronchiseptica, humans are host to the apparently specialized pathogen B. pertussis, the great majority having immunity due to vaccination, infection or both. Here we explore whether immunity to B. pertussis protects against B. bronchiseptica infection. In a murine model, either infection or vaccination with B. pertussis induced antibodies that recognized antigens of B. bronchiseptica and protected the lower respiratory tract of mice against three phylogenetically disparate strains of B. bronchiseptica that efficiently infect naïve animals. Furthermore, vaccination with purified B. pertussis-derived pertactin, filamentous hemagglutinin or the human acellular vaccine, Adacel, conferred similar protection against B. bronchiseptica challenge. These data indicate that individual immunity to B. pertussis affects B. bronchiseptica infection, and suggest that the high levels of herd immunity against B. pertussis in humans could explain the lack of observed B. bronchiseptica transmission. This could also explain the apparent association of B. bronchiseptica infections with an immunocompromised state.